A rare complication of pulmonary tuberculosis in childhood: Rasmussen`s aneurysm in a 9-year-old child with Down syndrome - Böncüoğlu, Elif; Çınar, Celal; Kıymet, Elif; Çağlar, İlknur; Kara, Aybüke Akaslan; Bayram, Nuri; Devrim, İlker (The Turkish Journal of Pediatrics, 2022)
Background. As an extremely rare entity reported in children, Rasmussen`s aneurysm is an inflammatory pseudo-aneurysmal dilatation of a branch of the pulmonary artery adjacent to or within a tuberculous cavity. Case. Here, we reported a 9-year-old child with Down syndrome who presented with massive hemoptysis. Endovascular coil embolization was performed for Rasmussen`s aneurysm. During the 2-year follow-up period, she had no further episodes of bleeding. Conclusions. In case of the development of massive hemoptysis in the follow-up of a patient with pulmonary tuberculosis and Down syndrome, this lethal complication should be considered.
Keywords: Down syndrome; child; rasmussen`s aneurysm; tuberculosis